2012
DOI: 10.1115/1.4005685
|View full text |Cite
|
Sign up to set email alerts
|

Using In Vivo Cine and 3D Multi-Contrast MRI to Determine Human Atherosclerotic Carotid Artery Material Properties and Circumferential Shrinkage Rate and Their Impact on Stress/Strain Predictions

Abstract: Background In vivo magnetic resonance image (MRI)-based computational models have been introduced to calculate atherosclerotic plaque stress and strain conditions for possible rupture predictions. However, patient-specific vessel material properties are lacking in those models which affect the accuracy of their stress/strain predictions. A non-invasive approach of combining in vivo Cine MRI, multi-contrast 3D MRI and computational modeling was introduced to quantify patient-specific carotid artery material pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The shrinking rate in the axial direction and shrinkage rates of lumen and outer wall (which have to be different) were determined so that (1) mass conservation is satisfied; and (2) the contours of the plaque and its components after pressurization and axial stretch achieve the best match with the in vivo geometry from MRI. A circular artery segment under in vivo condition goes through three stages to get its open-up zero-stress state: axial shrinkage (up to 30–50%; could be smaller for atherosclerotic plaques), circumferential shrinkage (5–20% based on our data, Huang et al, 2009; Liu et al, 2012b), and final opening-up with an opening angle (63.5°, n = 5) (Kural et al, 2012). Omitting any of the three stages would lead to stress/strain prediction errors on the order of 50–100% or even more (Liu et al, 2012b; Huang et al, 2009; Ohayon et al, 2007).…”
Section: In Vivo Image-based Fsi Models For Atherosclerotic Vulnermentioning
confidence: 62%
See 3 more Smart Citations
“…The shrinking rate in the axial direction and shrinkage rates of lumen and outer wall (which have to be different) were determined so that (1) mass conservation is satisfied; and (2) the contours of the plaque and its components after pressurization and axial stretch achieve the best match with the in vivo geometry from MRI. A circular artery segment under in vivo condition goes through three stages to get its open-up zero-stress state: axial shrinkage (up to 30–50%; could be smaller for atherosclerotic plaques), circumferential shrinkage (5–20% based on our data, Huang et al, 2009; Liu et al, 2012b), and final opening-up with an opening angle (63.5°, n = 5) (Kural et al, 2012). Omitting any of the three stages would lead to stress/strain prediction errors on the order of 50–100% or even more (Liu et al, 2012b; Huang et al, 2009; Ohayon et al, 2007).…”
Section: In Vivo Image-based Fsi Models For Atherosclerotic Vulnermentioning
confidence: 62%
“…A circular artery segment under in vivo condition goes through three stages to get its open-up zero-stress state: axial shrinkage (up to 30–50%; could be smaller for atherosclerotic plaques), circumferential shrinkage (5–20% based on our data, Huang et al, 2009; Liu et al, 2012b), and final opening-up with an opening angle (63.5°, n = 5) (Kural et al, 2012). Omitting any of the three stages would lead to stress/strain prediction errors on the order of 50–100% or even more (Liu et al, 2012b; Huang et al, 2009; Ohayon et al, 2007). Ohayon et al (2007) investigated the influence of residual stress/strain related to opening angle on the biomechanical stability of vulnerable coronary plaques and their potential impact for evaluating the risk of plaque rupture.…”
Section: In Vivo Image-based Fsi Models For Atherosclerotic Vulnermentioning
confidence: 62%
See 2 more Smart Citations
“…The mean opening angles for coronary and carotid samples were 120° and 63.5°, respectively. Liu et al (2012) introduced a finite element approach based on in vivo MRI Cine data to determine human carotid material properties. Their results from 12 patients showed that material stiffness measured by the effective Young’s modulus (YM) varied from 137 (soft), 431 (median), to 1435 kPa (stiff), respectively.…”
Section: Introductionmentioning
confidence: 99%